Antibacterial Effect of Jatropha multifida L. Leaf Infusion towards Staphylococcus aureus and Pseudomonas aeruginosa - Ivan Ivan; Sunarjati Sudigdoadi; Achmad Hussein S. Kartamihardja (Althea Medical Journal, 2019)
Background: Jatropha multifida is one of the medicinal plants commonly found in Indonesia. This plant is used in the community to heal open wounds, however, scientific evidence is lacking. The two most common bacteria which often cause infection in open wounds are Staphylococcus aureus and Pseudomonas aeruginosa. This study aimed to determine the antibacterial effect of J. multifida leaf infusion towards S. aureus and P. Aeruginosa in vitro.Methods: This was an experimental laboratory study conducted at the Microbiology Laboratory, Faculty of Medicine, Universitas Padjadjaran in 2014. The modified Kirby-Bauer antimicrobial diffusion procedure on Mueller-Hinton agar was applied to determine the inhibitory zone. In determining the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC), the modified technique of tube dilution was used.Results: The results of this research showed that the infusion of J. multifida leaves had inhibitory effects on the growth of S. aureus dan P. aeruginosa at the concentration of 100% and 75%. The minimum inhibition concentration and minimum bactericidal concentration could not be determined.Conclusions: There is evidence confirming the bacteriostatic antibacterial effect of J. multifida leaves which inhibits the growth of S. aureus and P. Aeruginosa. Further study is needed to explore J. multifida leaves.